PERANCANGAN DAN PENGEMBANGAN GAME MATCH THEM UP DENGAN MENGGUNAKAN METODE WATERFALL - Sandy Sugiyana; Yulisa Geni, Bias (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
Games have significant potential to support early childhood education, especially digital educational games for young children. However, the current dominance of foreign productions in game development is notable. In this study, the authors focus on early childhood as the target audience, recognizing children's preference for games over theoretical learning. To address this, the authors developed an educational game application that enables learning through play. The study employs the waterfall method in software engineering, utilizing Unity 3D and implementing C# for specific functions. The primary objective is to provide a learning avenue through an educational guessing game featuring animal pictures, aiming to enhance children's learning abilities. The research utilizes qualitative methods, including observations, interviews, questionnaires, and literature reviews, resulting in an appealing drag-and-drop game designed to contribute positively to early childhood education through educational game technology.